The Effects of Core Stabilization Trunk Muscle Fatigue on Lower Limb Stiffness of Basketball Players - Mehdi Khaleghi Tazji; Hassan Sadeghi; Ali Abbasi; Mohammad Aziminia; Ali Shahhosseini; Mohammad Ebrahim Marjani; George A. Koumantakis (MDPI AG, 2023)
Core stability is the ability to control the position and motion of the trunk over the pelvis and legs to allow the optimum production and transfer of force to the terminal segment in sporting activities. The effect of fatigue, especially core muscle fatigue, on stiffness as a performance index requires more study. This research aimed to investigate the effect of the core stabilization muscles' fatigue on lower limb stiffness during hopping. Thirty active basketball players participated in this study (age: 20.90 ± 1.49 years; weight: 60.30 ± 3.10 kg; height: 163.2 ± 5.04 cm). The hopping test (15 jumps) was performed before and after the fatigue protocol in three states including at a preferred (no frequency control), maximum, and 2.2 Hz frequency on the force plate. The stiffness of the lower extremities was measured before and after the fatigue protocol. The results of the dependent t-test showed core muscle fatigue led to reduced lower extremity stiffness under all three hopping-test conditions by 15.3-15.9% (p ≤ 0.005). It seems that core muscle function affects lower extremity stiffness, and can function as a performance index in athletes. Although performed in healthy volunteers, this study may have implications for injury prevention, highlighting the necessity to perform interspersed endurance training using the different body parts of the kinetic chain.